EFFICACY OF CONJUGATED LINOLEIC ACID (CLA) ON HUMAN HEALTH - Novack, Mariana Moura Ercolani; Cauduro, Lidia; Fuke, Gitane; Nörnberg, José Laerte (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This review covers aspects related to conjugated linoleic acid (CLA) and its relationship to disease. The term CLA represents a mixture of positional and geometric isomers of linoleic acid, of which two of these isomers (9c, 11t and 10t, 12c) have biological activity. Dairy products are the most abundant source of conjugated linoleic acid, which refers to a group of positional and geometric isomers of CLA (CLA 18:2 cis-9, cis-12). CLA has been investigated for its beneficial in the prevention and treatment of a variety of diseases, including obesity, cancer, diabetes and cardiovascular disease effects. Scientific information cataloging the physiological properties of CLA, which serve as inputs to argue its potential as a functional ingredient to be used in the prevention and control of several chronic metabolic disorders.